EFFECTIVENESS OF TEACHING SOCIAL STUDIES SUBJECT USING INFOGRAPHIC TECHNIQUES AND ITS EFFECT ON ACHIEVEMENT AND VISUAL INTELLIGENCE - Mahdi Jadir Habeeb (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
The researcher used the experimental design with partial control with two equal experimental and control groups, and according to this design, the research sample was randomly selected from the research community that represented (governmental middle and secondary schools in the Karbala Governorate Center affiliated to the General Directorate of Education of Karbala) and was (medium Thuraya for girls), was rewarded The researcher between the two groups in the following variables: chronological age calculated in months, intelligence, a test of previous information, the achievement of parents, previous achievement in the subject of social studies, and the scientific article identified the first three chapters (the first: the geography of the Arab world, the second: the Arab world (population and economic activity), Third: The conditions of the Arabian peninsula before Islam) from the book of Sociology for the second intermediate grade. The behavioral goals of these chapters were formulated, as their number reached in their final form (160) behavioral goals, and with regard to the two research tools, the researcher intentionally constructed the research tools that were represented by an achievement test in the subject of social studies consisting of (50) substantive paragraphs of the type of multiple-choice of four Alternatives As for the second tool, it consisted of the measure of visual intelligence towards the social matter, which is ultimate of (34) items. After applying the research tools and analyzing the results obtained statistically by using Microsoft Excel and SPSS, the results showed that the experimental group students who studied according to the infographic technique were superior to the control group students who studied according to the usual method of achievement and the visual intelligence scale.